1979
DOI: 10.1016/0304-3959(79)90050-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse noxious inhibitory controls (DNIC). II. Lack of effect on non-convergent neurones, supraspinal involvement and theoretical implications

Abstract: (1) Diffuse noxious inhibitory controls (DNIC) were tested for their effect on noxious only, non-noxious and proprioceptive cells in the dorsal horn of the intact anaesthetized rat. Unlike convergent neurones, as described in the previous paper, there was no effect of DNIC on these neurones. It is concluded that convergent neurones are specifically inhibited by DNIC. (2) The effect of DNIC could not be demonstrated for convergent neurones in the spinal animal. Thus the neuronal substrate for DNIC must involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
253
0
11

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 704 publications
(275 citation statements)
references
References 53 publications
11
253
0
11
Order By: Relevance
“…20 Indirect effects of acupuncture include remote analgesic effects of puncturing the skin with acupuncture needles 48,49 and psychosocial benefits of being treated by a clinician who creates an expectation of medical improvement. 50 Although such responses are generally regarded as placebo effects, the "intentional environment" created by acupuncturists has been identified as a component of acupuncture therapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Indirect effects of acupuncture include remote analgesic effects of puncturing the skin with acupuncture needles 48,49 and psychosocial benefits of being treated by a clinician who creates an expectation of medical improvement. 50 Although such responses are generally regarded as placebo effects, the "intentional environment" created by acupuncturists has been identified as a component of acupuncture therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of diffuse noxious inhibitory control (DNIC) was formulated from observations made with recordings of spinal dorsal horn units in anesthetized rats in response to peripheral stimuli applied to various parts of the body or electrical stimulation of peripheral nerves (124,125). It was found that peripheral noxious stimuli suppressed the neuronal responses of convergent dorsal horn units to either electrical stimulation of C-fibers or application of noxious heat (124,125).…”
Section: Diffuse Noxious Inhibitory Controls Modulation Of Painmentioning
confidence: 99%
“…Ao ser ativado, fibras noradrenérgicas e serotoninérgicas favorecem a liberação de encefalinas nos cornos posteriores da medula espinhal. Essa liberação de encefalinas inibe a percepção da dor de forma difusa (40)(41)(42) . Déficit nos mecanismos endógenos inibitórios de controle da dor, ou seja os CIDN, tem sido apontado como possível causa de alguns tipos de dor crônica (43,44) .…”
Section: Mecanismos Endógenos De Controle Da Dorunclassified